2022
DOI: 10.1038/s41366-021-01050-7
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial adipose tissue thickness is associated with increased COVID-19 severity and mortality

Abstract: Background Increased adiposity and visceral obesity have been linked to adverse COVID-19 outcomes. The amount of epicardial adipose tissue (EAT) may have relevant implications given its proximity to the heart and lungs. Here, we explored the role of EAT in increasing the risk for COVID-19 adverse outcomes. Methods We included 748 patients with COVID-19 attending a reference center in Mexico City. EAT thickness, sub-thoracic and extra-pericardial fat were measured using … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
2
10
0
4
Order By: Relevance
“…Our finding is partially in line with the previous reports from Mehta et al and Grodecki et al [1,10]. and this is not surprising considering that SARS-CoV-2 enters into cells using the ACE2 receptor, which is highly expressed in EAT and other visceral adipose depots [22].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding is partially in line with the previous reports from Mehta et al and Grodecki et al [1,10]. and this is not surprising considering that SARS-CoV-2 enters into cells using the ACE2 receptor, which is highly expressed in EAT and other visceral adipose depots [22].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that COVID-19 morbidity and mortality may be related to epicardial adipose tissue (EAT) [1] and visceral adipose tissue (VAT) [2], which may act as SARS-CoV-2 reservoir, thereby prolonging the viral spread inside the thorax [3].…”
Section: Introductionmentioning
confidence: 99%
“…The 80th gender-specific percentile of EAT thickness was obtained and used as the threshold to define increased EAT thickness. In addition, chest CT findings were recorded and used to evaluate severity of COVID infection ( 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…Comorbidities – Prevalence of diabetes and obesity in Mexican population are high and the impact of their impact on the course of the COVID-19 pandemic in Mexico have been widely reported 1,33,34 . To this end, we also evaluated vaccine effectiveness for individuals with diabetes and, secondarily, obesity.…”
Section: Methodsmentioning
confidence: 99%